Metodologías activas para mejorar el aprendizaje de las sucesiones matemáticas, sexto grado, Escuela de EB “Rosa Josefina Burneo de Burneo”, Loja, 2023-2024 - Pullaguari Caraguay, Jessica del Rocio (2024)
The research entitled Active methodologies to improve the learning of mathematical sequences, sixth grade, at Escuela de Educación Básica "Rosa Josefina Burneo de Burneo", Loja, 2023-2024; has as its general objective: To determine the influence of active methodologies in the learning of mathematical sequences at Escuela de Educación Básica "Rosa Josefina Burneo de Burneo", Loja, 2023 – 2024. The research adopted a qualitative and quantitative approach, descriptive and quasi-experimental design; in the methodology, the following methods were used: analytical, scientific, synthetic, statistical, descriptive; to gather information, the teacher was interviewed and the students were asked a survey with ten questions on active methodologies; the research population comprised one teacher and twentythree students; the initial findings determine that the learners investigated require considerable improvement in their skills, as well as in problem solving and active participation, which is why the methodological proposal called "The World of Mathematical Sequences" was designed and implemented, at the conclusion of its application, a second evaluation was carried out whose results indicate significant progress in the learning and understanding of mathematical sequences as they fostered reflective and reasonable thinking in the students, in contrast to a traditional approach focused on the repetitive use of texts and the lack of use of technology and other methodologies that could improve participation and knowledge acquisition, by encouraging their application we also managed to improve the learning of mathematical sequences by capturing attention, motivating learning, and stimulating students' creativity and interest in learning. Therefore, these results affirm the positive impact in terms of the application of active methodologies for learning mathematical sequences.